2018
DOI: 10.5586/aa.1745
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-term cold stress on enzymatic antioxidative defense system in chickpea (Cicer arietinum L.)

Abstract: Abiotic stresses such as cold, heat, and drought are the main causes of universal crop losses. Plants have generated adaptive responses which prevent them from oxidative damage caused by environmental stresses. The present research aimed to evaluate the effect of cold stress on lipid peroxidation and antioxidant enzyme activity in the leaves of eight cultivars / advanced lines of chickpea (<em>Cicer arietinum</em> L.). Three-week-old plantlets were subjected to cold stress (0°C) for 24 or 48 hours.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
2
2
1
Order By: Relevance
“…The enhanced production of H2O2 might be due to the imbalanced antioxidant enzyme activities (Figure 3a-c). These results demonstrated the adverse effects of chilling stress, i.e., stunted growth of rice seedlings through increasing ROS level and lipid peroxidation under chilling stress, that was in line with the previous studies on wheat [22,84], chickpea [85] and maize (Zea mays L.) [86]. On the other hand, exogenous application of NO to rice plants relieved adverse effects of chilling-induced oxidative stress, as supported by declined O2 •− , H2O2 and MDA contents in rice plants (Figure 2a-c), which was in accordance with previous findings in wheat [22], Chinese cabbage [23] and orange (Citrus sinensis) [87] under chilling stress.…”
Section: Discussionsupporting
confidence: 92%
“…The enhanced production of H2O2 might be due to the imbalanced antioxidant enzyme activities (Figure 3a-c). These results demonstrated the adverse effects of chilling stress, i.e., stunted growth of rice seedlings through increasing ROS level and lipid peroxidation under chilling stress, that was in line with the previous studies on wheat [22,84], chickpea [85] and maize (Zea mays L.) [86]. On the other hand, exogenous application of NO to rice plants relieved adverse effects of chilling-induced oxidative stress, as supported by declined O2 •− , H2O2 and MDA contents in rice plants (Figure 2a-c), which was in accordance with previous findings in wheat [22], Chinese cabbage [23] and orange (Citrus sinensis) [87] under chilling stress.…”
Section: Discussionsupporting
confidence: 92%
“…In other studies, in which chickpea was used as the experimental material, it was reported that low-temperature stress increased CAT and APX activity, but there was no change in SOD activity (Nazari et al, 2012;Yousefi et al, 2018). Contrary to these results, in this study, it was reported that only high-temperature stress significantly increased SOD, CAT, and APX activities compared to the control temperature (Fig.…”
Section: Changes In Physiological Parameterscontrasting
confidence: 81%
“…Of these proteins, 334 (39%) significantly increased > 1.5-fold in relative abundance (File S4) at one or more time points, with more (522; 62%) showing significant decreases > 1.5-fold (File S5). In line with the cold-induced membrane protection observed in electrolyte leakage assays (Figure 1), several protein families associated with cold stress were identified in our MS analysis including sugar transporters (sucrose transporter SUT1-like protein; Bradi1g73170.1; Tarkowski and Van den Ende 2015), dehydrins (dehydrin COR410-like; Bradi3g51200.1; Liu et al 2017), and ROS scavengers (catalase; Bradi1g76330.1; Yousefi et al 2018), and served to increase confidence in the analysis.…”
Section: Cold Acclimation Treatment Time and Quantifying Recovered Proteinssupporting
confidence: 70%